Analisis Penyelenggaraan Bimbingan Manasik Haji Di Kantor Urusan Agama Melalui Model Evaluasi - Ade Yuliar; Romadhani Anggika Putri (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2021)
Community knowledge regarding guidance on Hajj rituals is very limited. Kartasura Religious Affairs Office as a small part of the central government. Have responsibility for providing Hajj ritual guidance training for prospective pilgrims. With the Hajj ritual training is a form of training, in order to improve the skills of pilgrims. Both in accepting and understanding the material delivered in the guidance of Hajj rituals. This research was conducted to describe the 3 points of CIPP evaluation. Input evaluation includes clients (prospective pilgrims), and staff (presenters). Process evaluation (implementation) includes the program (material), and training schedule. Product evaluation (results) includes the results of interviews with pilgrims who have registered guidance for Hajj rituals at KUA Kartasura. Based on the results of the study, the Kartasura Religious Affairs Office provides services to pilgrims in accordance with procedures. Out of a total of 116 pilgrims taking part in the guidance of Hajj rituals at KUA Kartasura. Based on age, education, occupation, presenters, and pilgrimage ritual implementation schedules. It is in accordance with the Decree of the Director General of Hajj and Umrah Management. It's just that there is no manasik guide in KUA Kartasura that does not yet have a Hajj guidance certificate.